How the Wari fashioned trophy heads for display: A distinctive modified cranium from Cuzco, Peru, and comparison to trophies from the capital region - Andrushko, V.A. (The Bioarchaeology of the Human Head: Decapitation, Decoration, and Deformation, 2011)
Keywords: dept.ant

Emics and etics of health problems in Ethiopia - Messing, S.D. (Medical Anthropology, 2011)
Keywords: dept.ant

Social bioarchaeology - partnerships, pitfalls, and ethical concerns in international bioarchaeology - Turner, Bethany L.; Andrushko, Valerie A. (Wiley-Blackwell, 2011)
Keywords: dept.ant

Investigating a child sacrifice event from the Inca heartland - Andrushko, Valerie A.; Buzon, Michele R.; Gibaja, Arminda M.; McEwan, Gordon F.; Simonetti, Antonio; Creaser, Robert A. (Journal of Archaeological Science, 2011)
Human sacrifice in the Inca Empire at times took the form of the capacocha, a sacrificial rite involving the most beautiful children in the empire. In this study, we investigate a possible capacocha at the pre-Columbian site of Choquepukio in the Cuzco Valley of Peru. During excavations at Choquepukio in 2004, seven children (aged 3-12 years) were discovered buried together; accompanying them was an elaborate assemblage of high status artifacts similar to those from other recent archaeological finds that are believed to be capacocha sacrifices. Since colonial documents indicate that capacocha children were selected from diverse regions of the empire, we initiated a radiogenic strontium isotope analysis to determine the origins of the children found at Choquepukio. Our analysis showed that, indeed, two children in the assemblage had non-local origins. When considered together, the osteological, archaeological, and isotopic evidence suggest that a capacocha event occurred at Choquepukio, representing the only lower-elevation capacocha to have been found in the Cuzco region. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Andes; Bioarchaeology; Capacocha; Cuzco; Strontium isotope analysis; archaeological evidence; archaeology; artifact; dept.ant; isotopic analysis; strontium isotope

The pathological consequences of cranial vault modification: an analysis of human skeletal remains from Cuzco, Peru - Andrushko, Valerie A.; Messer, Diana Lynn (American Journal of Physical Anthropology, 2011)
Keywords: dept.ant; peer-reviewed; ⛔ No DOI found

Skeletal evidence for Inca warfare from the Cuzco region of Peru - Andrushko, Valerie A; Torres, Elva C (American Journal of Physical Anthropology, 2011)
This article addresses the bioarchaeological evidence for Inca warfare through an analysis of 454 adult skeletons from 11 sites in the Inca capital region of Cuzco, Peru. These 11 sites span almost 1000 years (AD 600-1532), which allows for a comparison of the evidence for warfare before the Inca came to power (Middle Horizon AD 600-1000), during the time of Inca ascendency in the Late Intermediate Period (AD 1000-1400), and after the Inca came to power and expanded throughout the Cuzco region and beyond (Inca Imperial Period, AD 1400-1532). The results indicate that 100 of 454 adults (22.0%) showed evidence of cranial trauma. Of these, 23 individuals had major cranial injuries suggestive of warfare, consisting of large, complete, and/or perimortem fractures. There was scant evidence for major injuries during the Middle Horizon (2.8%, 1/36) and Late Intermediate Period (2.5%, 5/199), suggesting that warfare was not prevalent in the Cuzco region before and during the Inca rise to power. Only in the Inca Imperial Period was there a significant rise in major injuries suggestive of warfare (7.8%, 17/219). Despite the significant increase in Inca times, the evidence for major cranial injuries was only sporadically distributed at Cuzco periphery sites and was entirely absent at Cuzco core sites. These findings suggest that while the Inca used warfare as a mechanism for expansion in the Cuzco region, it was only one part of a complex expansion strategy that included economic, political, and ideological means to gain and maintain control. Copyright © 2011 Wiley-Liss, Inc.
Keywords: *Archaeology; *Skull/in [Injuries]; *Warfare; Adolescent; Adult; Archaeology; Female; History, 15th Century; History, Medieval; Humans; Male; Middle Aged; Peru; Skull; War; Weapons; adult; archeology; article; battle injury; bioarchaeology; bone injury; conflict; dept.ant; history; human; imperialism; major clinical study; peer-reviewed; politics; skeletal injury; skeleton; skull injury; trauma; war; weapon

Partnerships, pitfalls, and ethical concerns in international bioarchaeology - Turner, Bethany L; Andrushko, Valerie A (Social Bioarchaeology, 2011)
Keywords: Culturally affiliated descent communities and bioarchaeologists - connections to human remains; Ethical issues, studying human remains - training students in bioarchaeology in united states; Ethical practice, central to bioarchaeology in united states - component of training in the field; Ethics and bioarchaeology in united states - issues of ethical practice in excavation; Human remains analyses - valuable bridges, between past and present; Language barriers and convoluted online submission processes - and additional obstacles; Non-destructive analyses - toward ethical practice in peruvian bioarchaeology; Partnerships, pitfalls and ethical concerns - in international bioarchaeology; Passage of NAGPRA - the native american graves protection and repatriation act of 1990; Practice of bioarchaeology in peru - influenced by cultural and political economic processes; dept.ant